Multi-GNSS PPP-RTK: Mixed-receiver network and user scenarios - Teunissen, Peter; Khodabandeh, Amir; Zhang, B. (2018)
In this contribution, we present full-rank observation equations of the network and user receivers, of mixed types, through an application of S-system theory. We discuss the important roles played by the inter system biases (ISBs), and we show how the three-component structure of PPP-RTK is affected by the inclusion of the ISBs as extra parameters in the model.